ANALISIS TREN KASUS PERSALINAN REMAJA AKHIR (15-19 TAHUN) DI WILAYAH KERJA DINAS KESEHATAN, PENGENDALIAN PENDUDUK DAN KELUARGA BERENCANA KOTA TANJUNGPINANG TAHUN 2019-2021 - Mia Afritia; Risnawati Risnawati; Tuti Susilowati; Nur Sri Atik; Helmy Apreliasari (Nusantara Hasana Berdikari, 2022)
Childbirth in adolescents is one of the high-risk factors for both the adolescents themselves and their babies and because of this, the opportunity to obtain education or work is reduced. This study aims to analyze the trend of late adolescent deliveries (15-19 years) in the work area of ​​the Department of Health, Population Control and Family Planning in Tanjungpinang city for the period 2019 to 2021. This research uses an analytical descriptive research method. The data was taken from the Department of Health, Population Control, and Family Planning in Tanjungpinang City from 2019 to 2021. The results showed that in 2019 there were 88 cases, in 2020 it increased to 103 cases, and in 2021 it was getting worse rising to 116 cases and Tanjungpinang public Health Center was the highest number of adolescent deliveries (15-19 years). The conclusion of this research is The trend in cases of late adolescent childbirth (15-19 years) in the work area of ​​the Tanjungpinang City Health, Population Control and Family Planning Office in 2019-2021 has increased. We can give suggestions so that programs and activities related to youth can be more considered and supported by policymakers in terms of funding and administration.